2014
DOI: 10.21608/ejm.2014.239
|View full text |Cite
|
Sign up to set email alerts
|

Pulping of Sugarcane Bagasse Using Ceriporiopsis subvermispora SS-33 and Ophiostoma piliferum as a Fungal Bio-agents

Abstract: AGASSE is an agricultural by product from sugar cane after the ….. cane is harvested and crushed to extract the juice. The utilization of bagasse as raw material for pulp and paper industry is increasing rapidly which also increasing pollution to the environment. In renewable resource to reduce chemical pollution, white rot fungi or lignin-degrading fungi was employed to contribute to remove lignin from raw materials. The aim of this investigation, is to determine the activity of white-rot fungi on bagasse as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Ceriporiopsis subvermispora seems to be the most suitable species for bleaching processes. Its co-culture with Ophiostoma piliferum could result in an additional decrease in the kappa number and better-quality properties of the paper (Gamal et al, 2014). However, C. subvermispora co-cultured with Physisporinus rivulosus or P. ostreatus showed no significant difference in delignification compared with axenic cultures (Chi et al, 2007).…”
Section: Biotechnological Applicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Ceriporiopsis subvermispora seems to be the most suitable species for bleaching processes. Its co-culture with Ophiostoma piliferum could result in an additional decrease in the kappa number and better-quality properties of the paper (Gamal et al, 2014). However, C. subvermispora co-cultured with Physisporinus rivulosus or P. ostreatus showed no significant difference in delignification compared with axenic cultures (Chi et al, 2007).…”
Section: Biotechnological Applicationsmentioning
confidence: 95%
“…Secondary analytical methods, such as Scanning Electron Microscopy (SEM), are used to confirm lignin degradation (Gamal et al, 2014;Feng et al, 2015;Zhou and Li, 2016;Meehnian et al, 2017;Kaur et al, 2018;Luo et al, 2020;Cui et al, 2021;Fatma et al, 2021;Li et al, 2021) and concluded that different co-cultures can accentuate plant cell wall degradation. The action of the fungi in the co-culture changed the initially smooth surface into an irregular surface material, with greater exposure to cellulose fibers, which can collapse, resulting in a flatter structure.…”
Section: Synergistic Co-culturesmentioning
confidence: 99%
See 1 more Smart Citation